2016
DOI: 10.1002/ajpa.22986
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Covariation between the Maxillary Sinus and Midfacial Skeleton among Sub‐Saharan and Circumpolar Modern Humans

Abstract: These results suggest that the maxillary sinus serves as a zone of accommodation at the confluence of multiple facial components, potentially minimizing effects of morphological alterations to certain components on adjacent structures. Am J Phys Anthropol 160:483-497, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 122 publications
19
67
0
Order By: Relevance
“…; Bastir & Rosas, ) as well as the vertical expansion of the maxillary sinus (‘secondary pneumatization’, Smith et al. ) as its shape has been found to covary with the midface (Butaric & Maddux, ; although see O'Higgins et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bastir & Rosas, ) as well as the vertical expansion of the maxillary sinus (‘secondary pneumatization’, Smith et al. ) as its shape has been found to covary with the midface (Butaric & Maddux, ; although see O'Higgins et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The forward growth observed in this region associated with bone formation in our sample may thus reflect this expansion. More generally, due to the central position of the maxilla in the craniofacial complex and the biological functions it supports (vision, mastication, and respiration as mentioned above), maxillary growth is likely to be influenced by growth of the surrounding bones and soft tissues (Moss & Young, 1960;Smith et al 2014;Goergen et al 2017), the basicranium Bastir & Rosas, 2016) as well as the vertical expansion of the maxillary sinus ('secondary pneumatization', Smith et al 2005) as its shape has been found to covary with the midface (Butaric & Maddux, 2016;although see O'Higgins et al 2006). Therefore, changes in the expression of bone modeling patterns are certainly a response to the complex integration patterns of the craniofacial components.…”
Section: Patterns Of Bone Modeling In the Human Maxillamentioning
confidence: 99%
“…The extent of the maxillary sinus, which is the most studied of the paranasal sinuses, is known to be influenced in New World monkeys by the relative dental size and the growth of adjacent skeletal structures of the maxilla; histomorphometric studies have confirmed that the growing maxillary sinus extends into areas without constraints (Smith et al, ). In humans, the maxillary sinus is larger in individuals with larger faces and it accommodates in the available space left by the lateral nasal walls: individuals with narrower nasal cavities present larger maxillary sinuses (Butaric & Maddux, ; Butaric et al, ; Holton et al, ). However, a recent study of Maddux and Butaric (), which compares samples of different geographic origins, shows that the maxillary sinus extends more laterally and more inferiorly in individuals with taller zygomaticomaxillary interfaces (e.g., taller midfacial skeletons) compared to individuals with shorter midfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Association between traits can be inferred by comparing the ontogeny (i.e., growth trajectories) of different modules or anatomical parts or by direct test of correlation between traits (Lieberman, ). Based on previous studies on different paranasal sinuses, it is expected that the FS is structurally and developmentally associated with other variables, such as: (a) cranial size (Curtis et al, ; Zollikofer et al, ); (b) dimensions of adjacent structures, for example, nasal size (Butaric & Maddux, ; Butaric, McCarthy, & Broadfield, ; Holton, Yokley, & Butaric, ; Maddux & Butaric, 2017); and c) bone thickness and thickness of the glabellar region, as the bony environment provides the space to enable/constrain FS expansion (Curtis et al, ; Farke, ; Vinyard & Smith, ). The ontogenetic analysis of the FS in relation to these structures provides insight into the underlying mechanisms (e.g., the opportunistic pneumatization hypothesis) that shape the observed morphological variation among populations and species (Prossinger, ).…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have investigated the frequency of MS pathology (Ikeda, 1996;Perloff et al, 2000;Sánchez Fernández et al, 2000;Slavin et al, 2005;Roberts, 2007) and the position of the MSO relative to specific nasal landmarks for surgical purposes (Myerson, 1932;Van Alyea, 1936;Prasanna and Mamatha, 2010;Souza et al, 2016), few studies have systematically investigated how variations in MS size and/or shape relate to MSO position (an exception being Souza et al, 2016, see below). While human MSs are often described as pyramidal in shape, with the medial wall acting as the base of the pyramid and its apex extending laterally toward the zygoma (Skillern, 1923;Amedee, 1993;Singh and Tabaee, 2016;Souza et al, 2016), the size and shape of the MS are extremely variable at both the population (Shea, 1977;Fernandes, 2004b;Holton et al, 2013;Butaric, 2015;Butaric and Maddux, 2016;Maddux and Butaric, 2017) and individual levels (Anagnostopoulou et al, 1991;Amedee, 1993;Miller and Amedee, 1997;Uchida et al, 1998;Kim et al, 2002;Fernandes, 2004a). Sex-differences in MS size and shape have also been discussed, although varying results have been obtained.…”
Section: Introductionmentioning
confidence: 99%